2019
DOI: 10.7717/peerj.7791
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced changes in the expression of antioxidant system genes for rice (Oryza sativa L.) and bread wheat (Triticum aestivum L.)

Abstract: BackgroundPlant cell metabolism inevitably forms reactive oxygen species (ROS), which can damage cells or lead to their death. The antioxidant system (AOS) evolved to eliminate a high concentration of ROS. For plants, this system consists of the seven classes of antioxidant enzymes and antioxidant compounds. Each enzymatic class contains a various number of genes which may vary from species to species. In such a multi-copy genetic system, the integration of evolutionary characteristics and expression data make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…However, in response to abiotic stresses, including H 2 O 2 treatment, TmCAT1 expression increased in roots but not in leaves [73]. Up to now, ten CAT genes have been identified and molecularly characterized in wheat, and a complex transcription pattern involving the up-and downregulation of different CAT genes under various conditions and stress treatments was also observed [74,75]. In our experiments, the CAT1 gene showed quite similar expression profiles in both wheat and einkorn plants, where the transcript abundance decreased after UV-B treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, in response to abiotic stresses, including H 2 O 2 treatment, TmCAT1 expression increased in roots but not in leaves [73]. Up to now, ten CAT genes have been identified and molecularly characterized in wheat, and a complex transcription pattern involving the up-and downregulation of different CAT genes under various conditions and stress treatments was also observed [74,75]. In our experiments, the CAT1 gene showed quite similar expression profiles in both wheat and einkorn plants, where the transcript abundance decreased after UV-B treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The authors emphasized the role of exogenous sulfur as an inductor of salt tolerance because of enhancement of SOD, POX, CAT, increasing of AsA, tocopherol, phenolics, and decreasing carotenoids and MDA during sulfur supply. The large-scale meta-transcriptome and complementary experimental analysis of antioxidant genes regulation in response to cold and water deficiency for rice and bread wheat were carried out ( Ermakov et al, 2019 ). As a result, patterns of regulation of different gene copies of AOS in response to stress were described, and cold response turned out to be more stable and homogeneous than salinity, perhaps due to peculiarities of used methods for stress conditions.…”
Section: Survey Methodologymentioning
confidence: 99%
“…On the other hand, transcriptomic data combined with multivariate data analysis and statistics is a powerful approach for describing regulation patterns of individual gene families. For instance, such an approach was useful for studying antioxidant gene dynamics in response to stresses (drought, cold) based on transcriptomic data and qPCR gene profiling [36]. As a result, authors identified prospective antioxidant genes involved in the stress response.…”
Section: Introductionmentioning
confidence: 99%